Accountability of Population Administration Services at the Tamalanrea Subdistrict Office in Makassar City - M. Awaluddin (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
Accountability of Population Administration Services in Tamalanrea District, Makassar City aims to find out how the accountability of population administration in the Tamalanrea sub-district office in Makassar City. This type of research is Qualitative descriptive research. Data collection techniques are carried out through observation, interviews and documentation. Technical data analysis used consists of data reduction, data presentation, and drawing conclusions. The results of this study show that the accountability of population administration at the Tamalanrea sub-district office in Makassar city in its implementation can be assessed based on each indicator, namely Legitimacy for policymakers, The existence of adequate moral quality, sensitivity, openness, optimal utilization of resources and efforts to increase efficiency and effectiveness, therefore it is necessary to make improvements for the implementation of population administration services in Tamalanrea Subdistrict , Makassar City.